Opportunities for Multi-Lingual Education in Nepal - Koirala, Bidya Nath (Journal of Education and Research, 2010)
The author on this paper was incorrectly recorded on the Website - The correct author is Bidya Nath Koirala (28/02/2013). For decolonizers language is a tool of domination (Awasthi, 2004; Bourdieu, 1977); for language groups it is a subjectivity and inter-subjectivity (Koirala, 2007); for utilitarian it is a vehicle to take people from the local to the global world (Khadka, 2007); for knowledge seekers and promoters it is a means to generate the hidden treasure of the subalterns’ wisdom (Guha, 2005); for linguists’ it is a way to save language (Khadka et.al., 2006; Khadka, 2007); for activists it is a means to activate people (Yonjan, 2007); for existentialists language is the socio-political, cultural, and linguistic identity (CRED, 2005; Chirag, 2001), and for pedagogues it is a means to made easy and dignified learning (Mallikarjun, 2002). It means language is the response to the situatedness (Leve & Wegner, 1992). To resolve these concerns one needs language of co-existence, reciprocal learning and teaching. Nepal has more than hundred languages with 15 scripts (Khadka, Magar, & Koirala, 2006; Koirala, Khadka, & Magar, 2008). Muslim children for example should learn at least three scripts together, the Urdu, the Devnagari, and the English. This situation looks for shared script. DOI: http://dx.doi.org/10.3126/jer.v2i0.7620 Journal of Education and Research Vol. 2, 2010 p.30-34